Role played by the organometallic fragment on the first hyperpolarizability of iron-acetylide complexes: a TD-DFT study - Mendes, Paulo J. (2012)
The static first hyperpolarizabilities (β) for a series of both substituted thiophene-acetylide ligands and the corresponding 5-monocyclopentadienyliron(II) complexes were determined by density functional theory (DFT) calculations. The effect on the hyperpolarizabilities by various donor and acceptor substituents in the thiophene-acetylide ligands was studied. The nature and role of the electronic excitation contributions to the first hyperpolarizability, using time-dependent DFT (TD-DFT) calculations, are rationalized in terms of the two-level model. Our calculations show that the organometallic fragment can form a very effective push-pull system in combination with electron-withdrawing substituents in the thiophene acetylide moiety, leading to enhanced static first hyperpolarizabilities. Also, an improvement of the magnitude of β is expected if solvation effects are taken into account.